Construction of a novel electrochemical sensor based on biomass material nanocellulose and its detection of acetaminophen. Issue 43 (28th September 2022) - Liu, Sichen; Yu, Yanbo; Ni, Kelu; Liu, Tongda; Gu, Min; Wu, Yingchen; Du, Guanben; Ran, Xin
Abstract : In this work, acidic sulfated cellulose nanocrystals (CNCs) were used as green carriers, and a novel composite material was synthesized and used to design sensors for paracetamol (AP) detection. Abstract : In this work, acidic sulfated cellulose nanocrystals (CNCs) were used as green carriers, and a novel composite material was synthesized and used to design sensors for paracetamol (AP) detection. There are negatively charged acidic sulfate groups on the surface of CNCs, which can enhance the electrostatic repulsion between nanoparticles, thereby increasing the stability and dispersibility of AgNPs in the system, making them less prone to agglomeration. Cationic pillar[5]arene (CP5) with a strong host–guest effect was used as a stable ligand for silver nanoparticles (AgNPs). AgNPs have good electrical conductivity and large specific surface area, which can significantly increase the peak current. In addition, CP5 has excellent supramolecular recognition performance, which can specifically recognize the guest molecule AP to form an inclusion complex, so that a large number of AP molecules are attached to the electrode surface, which is beneficial to the amplification of electrochemical signals. The prepared sensor is more attractive in terms of sensitivity and recognition performance; the host–guest binding constant was (3.37 ± 0.26) × 10 4 M −1, which can be obtained with good linearity ( R 2 = 0.996), low detection limit (90 nM, LOD = 3 σ / k, S/N = 3) and a wide linear range (0.5–500 μM). The electrochemical sensor showed good performance in quantitative analysis, stability, selectivity, reproducibility, and actual sample detection, providing high feasibility for real-time monitoring of paracetamol; it also provides a new idea for a green sensor.